Effects of providing EFL learners with additional online and face‐to‐face practise opportunities to promote active learning in higher education - Liu, Jingrong; Li, Shujun; Zhang, Wanfang (Journal of computer assisted learning, 2024)
Background Limited research on the effectiveness of additional online and face‐to‐face practise opportunities for promoting active learning among Chinese EFL learners in higher education. Current understanding of self‐regulated and collaborative learning theories in educational contexts. Objectives To establish the efficacy of interactive online and face‐to‐face practise opportunities for enhancing active learning among Chinese EFL learners. Methods Employed mixed methods research to assess the impact of different types of practise opportunities on 116 EFL learners. Utilised methodological triangulation of QUAN + QUAL data and one‐way ANOVA for interpretation. Results and conclusions The study demonstrated the effectiveness of integrating online and face‐to‐face practise opportunities to enhance active learning. Empirical evidence supports the pedagogical and theoretical benefits of these opportunities for promoting active learning among EFL learners. Lay Summary What is currently known about this topic Limited scholarly exploration of supplementary practise opportunities for active learning among Chinese EFL learners Existing understanding of self‐regulated and collaborative learning theories in educational contexts What does this paper add Establishes the effectiveness of interactive online and face‐to‐face practise opportunities for promoting active learning Provides empirical evidence supporting the integration of these opportunities to enhance active learning Implications for practise/or policy Advocates for the combined use of online and face‐to‐face practise opportunities to enrich engagement, problem‐solving, feedback, and motivation among EFL learners Suggests the development of instructional frameworks based on self‐regulated and collaborative learning theories for enhanced CALL courses